Giving Wings to one billion Indians - Sugant, R. (Indian Journal of Marketing, 2004)
The first successful low-cost airline is generally acknowledged to be Southwest Airlines in the United States, which pioneered the concept in 1971 and has been profitable every year since 1973. With the advent of aviation deregulation, the model spread to Europe as well, the most notable success being the Irish Ryan Air, founded in 1985. Low cost airlines have been slow in setting up business in Asia. The first one to start services was Air Asia of Malaysia in 2003.A typical low cost airline's business model is based on: • A single passenger class so as to ensure maximum number of seats. • A single type of aircraft thereby reducing training and servicing costs. • Simple fare scheme. • Open seating, which encourages passengers to board early. • Direct point-to-point flights. • Flying to less congested airports. • Short flights and fast turnaround times allowing maximum utilization of planes. • No catering and complimentary services. • No frequent flier or other promotional schemes. • Direct distribution.